The Path of an Eagle : How to Overcome and Lead After Being Knocked Down - Fantom, Jay (HighBridge Audio, 2022)
A real, emotional, and vulnerable story of one man's persistent courage to overcome some of life's worst and greatest challenges, while finding hope, healing, love, peace, and fulfillment along the journey of life. This book is a heartfelt, emotive, and hopeful account of one man's awe-inspiring journey to overcome the seemingly impossible-near-death experiences, abuse of all kinds, depression, anxiety, addictions, and eating disorders. It captures how he embraced the past with truth, courage, and sincerity to help others find the answers to what it really takes to overcome and lead a fulfilled and meaningful life after being knocked down. Jay Fantom invites us all to be brave and courageous as we follow him down what he calls "The Path of an Eagle." It is where we will find hope and strength in God, as He will enable us to spread our wings and take flight-because we weren't meant to stay on the ground. Despite the struggles attempting to keep us down, we were made for the skies . . . and to soar above the clouds.